Nutrients and water-forest interactions in an Amazon floodplain lake: An ecological approach - Aprile, Fabio; Darwich, Assad José (Acta Limnologica Brasiliensia, 2013)
Aim: Catalão Lake was surveyed between 2002 and 2011 with The aim of studying seasonality of The flow of nutrients between water, sediment and aquatic macrophytes. The role of The flood pulse and The ecological mechanisms influencing The forest-water interactions in The Amazon floodplain were discussed; Methods: Catalão Lake is located in The Amazon floodplain (03° 08'-03o 14' S and 59° 53'-59° 58' W), near The confluence of The Solimões and Negro rivers, approximately 3000 m from The port of CEASA, near The city of Manaus. It is considered to be a mixed water lake because it receives white waters rich in sediments from The Solimões River and black waters with humic substances from The Negro River. Physical and chemical parameters including C, N and P levels were studied in The diverse compartments, and a flux model was developed; Results: There is a strong nutritional (C, N and P) and ionic (Na+, K+, Ca2+, Mg2+, Cl-, HCO3-, CO32- and SO42-) flow from The rivers to The lake. The highest C:N:P ratio was found in Paspalum repens which, during periods of drought, played an important role in releaseing nutrients into The water. The connectivity of The lake with The rivers ensured a high variation of transparency and nutrient content, fundamental for biological processes. A model of The nutrient flow, interaction and connectivity between ecosystems, and The influence of The hydrological cycle has been developed.
Nutrientes e interações aquático-forestais em um lago da planície amazônica: Uma abordagem ecológica